Rekognisi Terhadap Peluang Bisnis Online Melalui Media Sosial dan Hubungannya dengan Minat Berwirausaha: Studi Kasus Mahasiswa Politeknik Negeri Bandung - Deddy Saefuloh (P3M Politeknik Negeri Bali, 2020)
The trend of social media use has been increasing and encompass almost all activities covering political and economic aspect of a country, including in Indonesia. In terms of social, cultural as well as economic aspects, the use of social media has shifted the pattern and tradition of how people buy products. This phenomenon would become business opportunity to be identified, captured and made into reality by young people especially by university students. This research is to uncover how far the students could recognize online business opportunity through social media and how it can affect on entrepreneurial students’ intentions. The research used quantitative method and use google form to collect data. The research takes place in Politeknik Negeri Bandung (POLBAN) and students of POLBAN as samples that taken through convenience sampling. The research uses descriptive analysis to analyse the data and regression analysis to find out the effect of students’ recognition of business opportunities on the students’ entrepreneurial intentions. The descriptive analysis shows that respectively the highest mean of students’ perception is on trust of social media, benefit of social media, and the lowest is on confidentiality and ease of use. The research also shows that there is a positive and significant influence of students’ recognition of online business opportunity on their entrepreneurial intentions as much as 41.5% and the rest should be caused by other factors.